2020
DOI: 10.1038/s41594-020-0510-9
|View full text |Cite
|
Sign up to set email alerts
|

The structure of a calsequestrin filament reveals mechanisms of familial arrhythmia

Abstract: Mutations in the calcium-binding protein calsequestrin cause the highly lethal familial arrhythmia catecholaminergic polymorphic ventricular tachycardia (CPVT). In vivo, calsequestrin multimerizes into filaments, but an atomic-resolution structure of a calsequestrin filament is lacking. We report a crystal structure of a human cardiac calsequestrin filament with supporting mutational analysis and in vitro filamentation assays. We identify and characterize a novel disease-associated calse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…The study investigated potential autosomal dominant variants in CASQ2 that have been linked to families with CPVT. 31 Based on the results of in vitro turbidity assays, the authors concluded that K180R and the other autosomal dominant CASQ2 variants decreased the ability of Casq2 to polymerize. Further investigation of the crystallized polymer mapped the K180 amino acid onto a potential interdimerization site of Casq2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study investigated potential autosomal dominant variants in CASQ2 that have been linked to families with CPVT. 31 Based on the results of in vitro turbidity assays, the authors concluded that K180R and the other autosomal dominant CASQ2 variants decreased the ability of Casq2 to polymerize. Further investigation of the crystallized polymer mapped the K180 amino acid onto a potential interdimerization site of Casq2.…”
Section: Discussionmentioning
confidence: 99%
“…Recent in vitro studies suggested that the K180R variant may affect the ability of Casq2 to form polymers. 10,31 Based on the Casq2 polymers visible on Western blot, polymer levels were not significantly decreased in K180R heterozygous and homozygous mouse lysates (Figure 3B). Other CRU (calcium release unit) protein levels (RyR2, triadin, and junctin) were also not significantly different in the K180R heterozygous and homozygous mouse cardiomyocytes (Figure 3C).…”
Section: K180r Does Not Affect Expression Levels Of Casq2 and Other J...mentioning
confidence: 95%
See 1 more Smart Citation
“…Because ESEs/ESSs in mammals and other vertebrates are conserved ( 17 ), we included human sequences that were orthologous to solved mammalian structures, both with and without evidence for metal identity in the crystal. Rare structures solved using yttrium and ytterbium ( 24 , 25 ) were also included. All retrieved sequences were cross-checked against UniprotID ( 21 ) and matched to nucleotide (nt) sequences of Ensembl (v. 104) transcripts ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, CASQ2 is the second most mutated gene in CPVT accounting for ~5% of cases [ 41 ]. Initially described as the recessive form of CPVT (CPVT2), autosomal dominant mutations have also been reported [ 47 , 48 , 49 ]. CPVT-linked CSQ2 mutations may result in impaired Ca 2+ buffering, multimer formation and/or RyR2 regulation [ 41 , 44 , 50 ].…”
Section: Physiological Ryr2 Regulatorsmentioning
confidence: 99%